IMPLEMENTASI PROBLEM BASED LEARNING BERBANTUAN GAMMA DALAM MENINGKATKAN MINAT BELAJAR PEMBELAJARAN SOSIOLOGI X-A SMAN 1 TAYAN HILIR - Pane, Sukma Putri; Prancisca, Stella; Zatalini, Adhalia; Asriati, Nuraini; Firmansyah, Andang (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2026)
This study aims to describe the implementation of the Gamma-assisted Problem Based Learning (PBL) model in enhancing students' interest in learning Sociology in class X-A at SMAN 1 Tayan Hilir. The study employs a qualitative approach with a descriptive research design. Data collection techniques include observation, in-depth interviews with Sociology teachers, students, and the Vice Principal in charge of Curriculum, as well as documentation. Data analysis is carried out interactively through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results show that the application of the Gamma-assisted PBL model can increase students' interest in learning, as indicated by improved focus, active participation in discussions, engagement in problem-solving, and better learning outcomes. Using Gamma as an interactive learning medium helps students understand the material through engaging visual displays and supports group collaboration. Although teacher guidance is still needed to verify the content generated by AI, overall, the PBL model assisted by Gamma is effective in increasing students' interest in learning Sociology.